Solving an industrially relevant quantum chemistry problem on quantum hardware - Nützel, Ludwig; Gresch, Alexander; Hehn, Lukas; Marti, Lucas; Freund, Robert; Steiner, Alex; Marciniak, Christian D.; Eckstein, Timo; Stockinger, Nina; Wolf, Stefan; Monz, Thomas; Kühn, Michael; et al. (Quantum Science and Technology, 2025)
Quantum chemical calculations are among the most promising applications for quantum computing. Implementations of dedicated quantum algorithms on available quantum hardware were so far, however, mostly limited to comparatively simple systems without strong correlations. As such, they can also be addressed by classically efficient single-reference methods. Here we calculate the lowest energy eigenvalue of active space Hamiltonians of industrially relevant and strongly correlated metal chelates on trapped ion quantum hardware, and integrate the results into a typical industrial quantum chemical workflow to arrive at chemically meaningful properties. We are able to achieve chemical accuracy by training a variational quantum algorithm on quantum hardware, followed by a classical diagonalization in the subspace of states measured as outputs of the quantum circuit. This approach is particularly measurement-efficient, requiring 600 single-shot measurements per cost function evaluation on a ten qubit system, and allows for efficient post-processing to handle erroneous runs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: quantum algorithms for chemical calculations; quantum chemistry; quantum computing; trapped ions

Variational Hamiltonian simulation for translational invariant systems via classical pre-processing - Mansuroglu, Refik; Eckstein, Timo; Nützel, Ludwig; Wilkinson, Samuel; Hartmann, Michael (Quantum Science and Technology, 2023)
The simulation of time evolution of large quantum systems is a classically challenging and in general intractable task, making it a promising application for quantum computation. A Trotter-Suzuki approximation yields an implementation thereof, where a higher approximation accuracy can be traded for an increased gate count. In this work, we introduce a variational algorithm which uses solutions of classical optimizations to predict efficient quantum circuits for time evolution of translationally invariant quantum systems. Our strategy can improve upon the Trotter-Suzuki accuracy by several orders of magnitude. It translates into a reduction in gate count and hence gain in overall fidelity at the same algorithmic accuracy. This is important in noisy intermediate scale quantum-applications where the fidelity of the output state decays exponentially with the number of gates. The performance advantage of our classical assisted strategy can be extended to open boundaries with translational symmetry in the bulk. We can extrapolate our method to beyond classically simulatable system sizes, maintaining its total fidelity advantage over a Trotter-Suzuki approximation making it an interesting candidate for beyond classical time evolution.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Hamiltonian simulation; noisy intermediate scale quantum; time evolution; translational invariance; Trotter-Suzuki decomposition; variational algorithms